2009
DOI: 10.1091/mbc.e08-06-0566
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Renal Epithelial Tight Junctions by the von Hippel-Lindau Tumor Suppressor Gene Involves Occludin and Claudin 1 and Is Independent of E-Cadherin

Abstract: Epithelial-to-mesenchymal transitions (EMT) are important in renal development, fibrosis, and cancer. Loss of function of the tumor suppressor VHL leads to many features of EMT, and it has been hypothesized that the pivotal mediator is down-regulation of the adherens junction (AJ) protein E-cadherin. Here we show that VHL loss-of-function also has striking effects on the expression of the tight junction (TJ) components occludin and claudin 1 in vitro in VHL-defective clear cell renal cell carcinoma (CCRCC) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 66 publications
4
55
1
Order By: Relevance
“…It seems that PKD down-regulates claudin-1 at the mRNA level. Several reports have shown that transcription factors SP1, Cdx1, Cdx2, and GATA-4 positively regulate claudin-1 expression, whereas transcription factors SLUG, SNAIL, and HIF␣ act as repressors of claudin-1 expression in epithelial cells (52)(53)(54). SNAIL also down-regulates other junctional molecules, including E-cadherin and occludin; thus, it is a trigger of epithelial-tomesenchymal transition (14,53).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that PKD down-regulates claudin-1 at the mRNA level. Several reports have shown that transcription factors SP1, Cdx1, Cdx2, and GATA-4 positively regulate claudin-1 expression, whereas transcription factors SLUG, SNAIL, and HIF␣ act as repressors of claudin-1 expression in epithelial cells (52)(53)(54). SNAIL also down-regulates other junctional molecules, including E-cadherin and occludin; thus, it is a trigger of epithelial-tomesenchymal transition (14,53).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that EMMPRIN increases hypoxia-inducible factors (HIF 1 and 2) in both endothelial cells and in melanoma tumor cells. 38 These transcription factors were shown to down-regulate occludin and to disrupt tight junction, 39 thus representing an additional potential mechanism for the regulation of occludin by EMMPRIN in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α expression increases endothelial barrier permeability [165] and interferes with tight-and adherens junctions [166]. 28C).…”
Section: Spry2 Knockout Results In Loss Of Contact Inhibition and Endmentioning
confidence: 99%